THE SOLAR-RADIATION PRESSURE EFFECTS ON THE ORBITAL EVOLUTION OF ASTEROID MOONS - Troianskyi, V. V.; Bazyey, O. A. (Одеські астрономічні публікації, 2016)
In the theory of motion, disturbances are divided into gravitational and non-gravitational ones. In this paper, we discuss the effects of solar-radiation pressure on the orbital evolution of asteroid moons. It is known from the laws of physics that the smaller an object is the more pressure is exerted on it by solar radiation. That is the reason why asteroid moons with their small sizes are exposed to the solar-radiation pressure so much.